Effectiveness of wellbeing development program for youths at Ban Mutita Juvenile Vocational Training Centre for Boys - aranyasot, Thidarat; Srimoragot, Pongsri; Chaiyadej , Udomkan; Krasasom, Peerawet (Thai Journal of Nursing, 2023)
The objective of this quasi-experimental research was to examine effectveness of the wellbeing development program for child and youth at Ban Mutita Juvenile Vocational Training Centre for Boys, Nakhon Pathom Province. A sample of 25 child and youth, was purposively selected. Research tools were the wellbeing assessment and the wellbeing development program including food consumption, exercise and physical activity, stress management and emotional coping, smoking cessation and smoke-free environment. Data collection were done using the wellbeing assessment at the pre and post experimental periods and a 6-month follow-up of smoking cessation. Data were analyzed using descriptive statistics and paired t-test. The results reveal that the wellbeing development program cannot affect the youths’ wellbeing in total. In the wellbeing subparts, after the 2-month implementation of the wellbeing development program, youths gain better knowledge on food consumption, stress management and smoke-free environment at p < .05 ( t = 4.27, -6.28 and -7.19 respectively ). In contrast, their food consumption frequencies, food preference and exercise are not at good levels ( t = 7.80, 9.32 and 12.70 respectively ). On smoking cessation, at the 3-month and 6-month follow- up, 44 % and 48% of youths can stop smoking.